Estrategias pedagógicas y su incidencia en el rendimiento escolar en estudiantes de básica superior de la unidad educativa Junín del cantón Buena Fe período académico 2021-2022 - Peñafiel Arteaga, Miryam Elizabeth (2022)
In the present work, the incidence of pedagogical strategies in school performance in students of higher basic education is determined. The research was established with a qualitative-quantitative, descriptive and field methodology, applied to 11 teachers and 84 students in the Junín Educational Unit, of the Buena Fe canton. The data were analyzed using the Excel program, and the results they made viable the generation of alternatives regarding active strategies for the improvement of school performance. It was established that 33% of the students surveyed reported that their teachers promote active participation in the classroom, and 64% of teachers consider that they constantly promote collaborative learning. Finally, a training plan in pedagogical strategies was proposed, conceived as an educational, methodical and constituted process, through which in the short term the teacher must acquire the information, skills and methodologies required, to obtain results that arrive to benefit them with the required skills.